Recovery From Mobility Limitation in Middle-Aged African Americans: The Jackson Heart Study. (19th October 2020) - Odden, Michelle C; Sims, Kendra D; Thorpe, Roland J; Sims, Mario; Dhamoon, Mandip; Min, Yuan-I; Correa, Adolfo
Abstract: Background: Despite evidence that African Americans shoulder a high burden of mobility limitation, little is known about factors associated with recovery. Method: Participants from the Jackson Heart Study underwent 3 in-person exams from 2000 to 2013. Mobility limitations were assessed over this period by self-reported limitations in walking half a mile or climbing stairs during annual phone calls. The outcome of interest, recovery from mobility limitation, was defined as no mobility limitation the year following an incident event. Candidate predictor variables were assessed in logistic regression models, including sociodemographic, psychosocial, and health measures. Inverse probability weights were used to address missing data in the outcome. Results: Among 4526 participants (mean [ SD ] age = 54.5 (12.8) years) without a mobility limitation at baseline, 1445 (32%) had an incident mobility limitation over 12 years of follow-up, and 709 (49%) reported recovery from mobility limitation by 1 year later. Low income and daily discrimination were associated with a lower likelihood of recovery even after adjustment for covariates. In adjusted models, greater comorbidity was associated with a lower likelihood of recovering ( p -value for trend = .05). History of heart failure and cancer were associated with a lower likelihood of recovering from mobility limitation (OR: 0.52, 95% CI: 0.29, 0.94 and OR: 0.74, 95% CI: 0.55, 1.00). Adiposity, smoking status, and physical activity were not associated with recovery from mobility limitation. Conclusion: Half of incident mobility limitations in this population of middle-aged African Americans were transient. Adverse sociodemographic factors and comorbidities were associated with lower likelihood of recovery.